Chronic Prostatitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article contains information from local and foreign literature about the factors causing chronic prostatitis, clinical symptoms, types, complications, treatment and prevention. Information on the course, diagnosis and prevention of chronic prostatitis, acute and chronic bacterial prostatitis and chronic pelvic pain syndrome is presented.